Constitutional equality and the women's right - Trivedi, B.R. (New Delhi : Cyber Tech, 2010)
With special reference to India.
Includes bibliographical references and index.
Keywords: Women's rights; Women's rights -- India; Equality before the law; Equality before the law -- India